Organisational Culture and its Effect on Employee Performance - Rizwan J. Ahmad (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
Organisational culture encompasses the values, beliefs, and behaviors that determine how a company's employees and management interact and handle business transactions. This research examines the intricate relationship between organisational culture and employee performance, focusing on how the former influences productivity, motivation, job satisfaction, and overall performance. Using a robust theoretical framework, empirical data, and comparative analysis, this study sheds light on the critical role of culture in shaping workforce effectiveness. The findings suggest that a positive and well-managed organisational culture significantly enhances employee performance, while a toxic or misaligned culture can impede productivity and morale.